Moderate pyridoxal phosphate deficiency enhances neuronal excitability and promotes calcium dysregulation - Girgis, Valerie; Tharington, Ashlyn; Trivett, Jadyn; Fitting, Sylvia; Meeker, Rick B.; Rubinos, Clio (Frontiers in Neuroscience, 2025)
ObjectivePyridoxal 5′-phosphate (PLP), the active form of pyridoxine (vitamin B6), is essential for converting glutamate into the inhibitory neurotransmitter gamma-aminobutyric acid (GABA). Severe consequences of PLP deficiency due to genetic defects are well known, but the impact of modest pyridoxine deficits remains unclear. Low pyridoxine levels have been associated with poor neurological outcomes in disease and injury, but it is uncertain whether this reflects a causal relationship or is a secondary consequence of inflammatory conditions. This study aimed to investigate the functional impact of moderate reductions in PLP activity on neuronal function.MethodsPrimary mouse neuronal cultures were treated with amino-D-proline (ADP) to induce a moderate reduction in PLP activity to simulate a low pyridoxine environment. ADP concentrations were titrated to produce a small decrease in GABA expression without loss of GABAergic cells or innervation. Calcium signaling was assessed in live cells, and electrophysiological recordings were performed using multielectrode arrays to evaluate neural activity under baseline and mild pathological conditions (reduced magnesium, inflammatory environment).ResultsADP-treated neurons exhibited increased calcium signaling frequency and intensity, consistent with a hyperactive phenotype. Under mild pathological conditions, calcium signaling and accumulation were further amplified. Electrophysiological recordings revealed increased neural activity, characterized by a higher frequency of short bursts of synchronous activity and random spikes. Chronic ADP treatment led to compensatory changes in neural activity, suggesting potential differences between acute and chronic pyridoxine deficiency.ConclusionThis study demonstrates that even a modest reduction in PLP activity induces transient neuronal hyperexcitability, which may enhance the pathological effects of disease, injury, and inflammation. These findings highlight the importance of pyridoxine in maintaining neural stability and suggest that low pyridoxine levels could contribute to neurological dysfunction. Further investigation is warranted to fully understand the clinical implications of mild pyridoxine deficiency.